2003
DOI: 10.1046/j.1365-2850.2003.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

The clients’ experience of the community group: implications for nurse facilitators

Abstract: Community or large group meetings occur in many mental health units. Literature is available that describes the possible functions of such groups, but little is known about how they are actually experienced by the members, or the implications of this for nurse facilitators, especially in the current context of inpatient care. The aim of this study was to develop an understanding of the clients' experience of the daily community group in a unit that offered both an inpatient and a day patient service for adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Further studies have involved evaluations of therapeutic groups in a variety of settings. Harms & Benson (2003) examined clients' experiences of a community group which was facilitated by nurses. The findings indicated that the participants experienced the group as an anxiety‐provoking event especially in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have involved evaluations of therapeutic groups in a variety of settings. Harms & Benson (2003) examined clients' experiences of a community group which was facilitated by nurses. The findings indicated that the participants experienced the group as an anxiety‐provoking event especially in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Searching the literature for evidence of the community meeting purposes as discussed in the literature review section, reveals that all the studies and papers agreed that community meetings will be of benefit to the patients as wel as the staff (Winer, Klamen, 1997;Novakovic, Francis, Clark, & Caring, 2010;Fiddler et al, 2010;Benson, Harms, 2003;Lanza, Rierdan, Forester, Zeiss, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another qualitative research article was done by Benson, Harms (2003). This study builds up an understanding of the client's experience according to daily community meetings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations